Education According To The Thought Of Priest Al-Ghazalid And Its Relevance With Education Of Character In Indonesia - Lily Arliya (Medina-te : Jurnal Studi Islam, 2020)
The focus of this research is "Moral Education According to Imam Al Ghazali's Thought and its Relevance Study with Character Education in Indonesia". This study needs to be carried out to contribute morals and character in the current era of world globalization, especially the formation of morals and character for students, educators and educational staff. Moral education and character education are the keys to true happiness. In order for humans to have good noble morals (akhlakul karimah) and not cause destruction, Allah SWT sent the Prophet Muhammad to improve human morals. This research is a library research. The author examines the values ​​of moral education contained in the book "Ihya Ulumuddin" Imam al-Ghozali, and examining character education in Indonesia, the implementation of the 2013 curriculum, which contains the inculcation of character values ​​which include; Religious character, Honest, Tolerance, Discipline, Hard work, Creative, Independent, Democratic, Curiosity, National spirit or nationalism, Love of the motherland, Respect for achievement, Communicative, Love peace, Love to read, 16) Environmental Care, Social Care, Responsibility answer. The technique of collecting data is by digging up library materials that are relevant to the object of discussion being studied. The approach used is descriptive. While the analysis uses content analysis, which is a method that uses systematic techniques to analyze the contents of the data and review the data. Creative, independent, democratic, curiosity, spirit of nationality or nationalism, love of the homeland, respect for achievement, communicative, love peace, love to read, 16) environmental care, social care, responsibility. The technique of collecting data is by collecting the materials that are relevant to the object of discussion being studied. The approach used is descriptive with content analysis, which is a method that uses systematic techniques to analyze the contents of the data and review the data.